1981
DOI: 10.1172/jci110026
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Study of Vascularized Free-Draining Intraperitoneal Pancreatic Segmental Allografts in Beagle Dogs

Abstract: A B S T R A C T The purpose of the present study was to evaluate the significance of immunogenetic factors on the survival of pancreatic allografts in beagle dogs. Donors and recipients were leukocyte antigen (DLA)-typed and mixed lymphocyte culture (MLC)-tested. Recipients were made diabetic by total pancreatectomy and immediately implanted intraperitoneally with a vascularized, free-draining (duct unligated) pancreatic segmental (FDPS) allograft. Two groups of dogs were studied. In group I consisting of don… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1981
1981
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…However, insulin levels then declined as hyperglycaemia occurred. In contrast, Kyriakides et al [58] found that changes in glucose clearance during glucose tolerance tests or in serum insulin response did not precede rejection, and that the occurrence of hyperglycaemia was rapid and unpredictable. They were, however, able to demonstrate changes in cell mediated lymphocytotoxicity .against the donors before overt rejection.…”
Section: Immunological Aspects Of Pancreatic Allotransplantationmentioning
confidence: 92%
See 3 more Smart Citations
“…However, insulin levels then declined as hyperglycaemia occurred. In contrast, Kyriakides et al [58] found that changes in glucose clearance during glucose tolerance tests or in serum insulin response did not precede rejection, and that the occurrence of hyperglycaemia was rapid and unpredictable. They were, however, able to demonstrate changes in cell mediated lymphocytotoxicity .against the donors before overt rejection.…”
Section: Immunological Aspects Of Pancreatic Allotransplantationmentioning
confidence: 92%
“…Blood glucose and insulin levels during glucose or tolbutamide tolerance tests have been variously reportedly as low, normal or elevated [9,17,18,24,28,34,36,40,[53][54][55][56][57][58]. The factors responsible for the different results are difficult to sort out because of the variations in the models studied.…”
Section: Metabolic Efficiency Of Whole or Segmental Pancreatic Tramentioning
confidence: 99%
See 2 more Smart Citations
“…The technique of transplantation has previously been described [11]. Briefly, the tail of the pancreas was implanted heterotopically in the peritoneal cavity with the duct unligated and opening intraperitoneally [12]. End-to-side arterial anastomosis between the proximal splenic artery and the aorta, and endto-side venous anastomosis between the splenic vein and inferior vena cava was carried out, thus establishing venous drainage of the pancreas into the systemic circulation.…”
Section: Vascularized Segmental Pancreatic Transplantationmentioning
confidence: 99%